Evaluation of Antibiotic Use in the Inpatient Internal Medicine Ward at RSUD Ulin Banjarmasin - Nata Asi, Seva Bela; Aryzki, Saftia; Anggoro Mukti, Yusuf; Yuwindry, Iwan (Media Farmasi: Jurnal Ilmu Farmasi, 2025)
The misuse of antibiotics is a significant concern due to the potential for developing resistance, which poses a growing global health threat. In the United States, antibiotic-resistant infections impact two million individuals annually, leading to 23,000 deaths. In Indonesian hospitals, antibiotic prescription rates are high, ranging from 44-97%, with 30-80% of these prescriptions being inappropriate. This study aims to evaluate the use of antibiotics in the internal medicine inpatient ward at Ulin Hospital, Banjarmasin, both quantitatively and qualitatively, using the ATC/DDD and Gyssens methods. A descriptive observational study was conducted using retrospective data collected from January to December 2023. The analysis included prescription data from inpatients in the internal medicine ward. Several antibiotics were identified, including Ceftriaxone, Azithromycin, Levofloxacin, Moxifloxacin, Cefixime, and Cefotaxime. The total DDD value was found to be 118.69 DDD/100 inpatient days. The DU 90% analysis showed the following usage rates: Ceftriaxone (oral) 52.51%, Azithromycin (parenteral) 60.55%, Levofloxacin (oral) 68.10%, Moxifloxacin (parenteral) 75.21%, Cefixime (parenteral) 81.02%, and Cefotaxime (oral) 86.09%. Ceftriaxone was the most frequently used antibiotic, with 39 patients receiving appropriate prescriptions (category 0) according to the Gyssens method. In conclusion, Ceftriaxone was the most commonly used antibiotic, representing 36.90% of prescriptions. The evaluation using the ATC/DDD method yielded a total DDD/100 inpatient days value of 118.69, while the Gyssens method indicated that 33.33% of prescriptions were appropriate.